Review on the performances and applications of mesh-fabrics. (17th October 2022) - Liu, Lele; Ma, Pibo
Mesh-fabrics that enable flexible designability and structural mechanical load-bearing have been developing rapidly in the past several decades. Currently, there is an increasing demand for mesh-fabrics with lightweight and high strength in engineering fields. Nevertheless in practice, design, manufacture, and application of mesh-fabrics are often dealt with separately, which could lead to the performances of final products unable to meet the need of specific scenes. This article introduced the classifications and preparation processes of mesh-fabrics. The mechanical properties under various load conditions were described. Then different methods of structural and numerical simulations were reviewed. Current application status of mesh-fabrics were summarized; Finally, several suggestions have been provided to address challenges for the research, development, and application of mesh-fabrics. Look forward to the future, it is expected that mesh-fabrics will play a key role in innovative and high technology engineering fields.